Some estimates of the book collection accession dynamics in the Library on Natural Sciences of the Russian Academy of Sciences - N. E. Kalenov (Библиосфера)
The paper analyzes data on the flow of non-periodical publications entering the collections of the Centralized Library System headed by the Library for Natural Sciences of the Russian Academy of Sciences (LNS RAS). The analysis is carried on for a five-year interval (2013-2017). It gives the general annual quantitative characteristics of domestic and foreign publications acquisition. The author shows a sharp drop in the number of incoming foreign, as well as translated publications, on natural sciences. The article presents the efficiency analysis of receipting publications on a legal copy (LC), which shows that the efficiency (a share of publications for the current year in LC flows), although slightly increasing over the past year, remains rather low. Publications of 2017 not received by LNS RAS in the LC flow have been identified, and their reconciliation with the Russian State Library catalog has been carried out.